Integrating INDOBLIGHTCAST forecasting with fungicide scheduling for sustainable management of potato late blight, Phytophthora infestans in southern India - Priyank Hanuman Mhatre; K.L. Divya; Santosh Watpade; S. Subhash; Praveen S. Patted; P. Janani; Aarti Bairwa; Sanjeev Sharma; Brajesh Singh (Crop Protection, 2026)

Understanding the brown planthopper (Nilaparvata lugens Stål) resistance in rice through biological and biochemical responses - Darshana Brahma; S. Rajna; Subhash Chander; C.N. Rajarushi; Ranjith Kumar Ellur; Jessa Joseph (Crop Protection, 2026)

Microbial-mediated phosphorus management under zero-tillage enhances maize productivity, P-use efficiency, and carbon management in a maize-wheat system - Amit Kumar; U.K. Behera; Shivadhar; Subhash Babu; Raghavendra Singh; Saurav Saha; Anil K. Choudhary; Adarsh Kumar; Gaurendra Gupta; B.A. Gudade; Anup Das; Vijay Singh Meena; et al. (Field Crops Research, 2026)

Application of machine learning tools for prediction of seed cotton yield in upland cotton (G. hirsutum L.) under irrigated ecosystem - Debashis Paul; Vinita Gotmare; M. Saravanan; Sandeep Bagri; Harish Kumbhalkar; Subhash Chandra; S. K. Verma; Rishi Kumar; Y. G. Prasad (Euphytica, 2026)

Unravelling metal chelating activity, cytotoxicity, and seed germination of phytomediated cupric oxide nanoparticles - Alaa Kayali; Infant Santhose Barthelomai; Subhash Bharathi S; Gideon Paul Kingsly Jesurajan; Mohammed Ali Najjar (Nanotechnology for Environmental Engineering, 2026)

Interactive Effects of Elevated CO2, Temperature, and Weed Competition on Mungbean - Dasari Sreekanth; Deepak Vishwanath Pawar; Rajeev Kumar; Shobha Sondhia; P. K. Singh; J. S. Mishra; Ankita Sinha; Subhash Chander; Nagaraju Mukkamula; B. Kiran Kumar (Agricultural Research, 2026)

OnabotulinumtoxinA Alters Pro- and Anti-Inflammatory Dural Macrophage Response to CSD in Female Mice - Aaron J. Schain; Diego Delgado Fajardo; Andrew M. Strassman; Subhash Kulkarni; Ron S. Broide; Amy D. Brideau-Andersen; Aubrey Manack Adams; Mitchell F. Brin; Rami Burstein (Toxicon, 2026)

Weed Management in Fodder Maize Using Herbicides Under Diverse Agro-Climates of India - R. K. Agrawal; Jeetendra Kumar Soni; S. K. Jha; R. V. Kale; Rajesh Kumar; Birendra Kumar; Usha C. Thomas; Subhash Chand; A. K. Roy; A. K. Jha; V. K. Yadav (International Journal of Plant Production, 2026)

Augmenting Seed Potato Production Through Integration of Aeroponics, Apical Rooted Cuttings and Sprout Cutting Techniques: A Comprehensive Review - Murlidhar J. Sadawarti; S. P. Singh; Tanuja Buckseth; Vinod Kumar; Rajesh K. Singh; Ashwani K. Sharma; Subhash Katare; Pooja Jatav; Deepanshi Deora; Priyadarshani Khambalkar; R. K. Samadhiya; Brajesh singh (Agricultural Research, 2026)

The in vitro and in silico investigations on the α-amylase inhibitor derived from Leptadenia lanceolata (Poir.) Goyder leaf extract - Salman Abubakar Adam; Infant Santhose Barthelomai; Subhash Bharathi S; Alaa Kayali; Rajesh Kanna Gopal (Natural Product Research, 2026)

Articulating the multifaceted application of bioactive compound decorated silver/gold nanoparticles: Current and future prospective - Pooja V. Nagime; Vaishali S. Chandak; Shreya Kotnala; Mukesh Pandey; Titilope John Jayeoye; Sheeba Shafi; Subhash Chandra; Shradhanjali Singh; Vijay R. Chidrawar; Sudarshan Singh (Biocatalysis and Agricultural Biotechnology, 2025)

In Vivo Seed Potato Production Possibilities Through Sprouts - Tanuja Buckseth; M. J. Sadawarti; Pooja Jatav; Rajesh K. Singh; Jagesh K. Tiwari; Vinod Kumar; Ashwani K. Sharma; Subhash Katare; S. P. Singh; Brajesh Singh (Potato Research, 2025)

Soil Carbon and Nutrient Cycling Regulated by Fine Roots Distribution and Dynamics in Teak (Tectona grandis L.)-Based Agroforestry System in Semi-Arid Central India - Asha Ram; Shubham Choure; Inder Dev; Naresh Kumar; Deepak Singh; Dhiraj Kumar; Sovan Debnath; S. Suresh Ramanan; Ashutosh Dwivedi; Raju Kumar; Sanjana Maurya; Subhash Babu; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Graphene oxide liquid crystal membranes offer precise molecular sieving - Sk Safikul Islam; Anjali Kumari; Shabnam Pathan; Ria Sen Gupta; P. Rajasekhar Reddy; S. Arya; Subhash Kumar; Yagnaseni Roy; K. Anki Reddy; Suryasarathi Bose (Chemical Engineering Journal, 2025)

Functional response of temperature tolerant and control strain of Aenasius arizonensis against different densities of Phenacoccus solenopsis Tinsley - Kirankumar G N; Sachin S. Suroshe; Chaitanya M; K. Srinivas; Keerthi M C; Subhash Chander (Phytoparasitica, 2025)

In Vitro Effects of Cytochalasin D on Mitochondrial Energetic Markers, Nitric Oxide and Reactive Oxygen Species Status in Brain/Gut Axis of Climbing Perch (Anabas testudineus Bloch) - S. Rekha; M. C. Subhash Peter (Proceedings of the Zoological Society, 2025)

Comparative Study on Key Time Series Models for Exploring the Agricultural Price Volatility in Potato Prices - S. Vishnu Shankar; Ashu Chandel; Rakesh Kumar Gupta; Subhash Sharma; Hukam Chand; A. Aravinthkumar; S. Ananthakrishnan (Potato Research, 2025)

Quantitative Analysis on Expression of Insecticidal Crystal Proteins in Different Plant Parts of BG-II Cotton Hybrids at Various Phenological Stages - Debashis Paul; Rishi Kumar; G. Balasubhramani; Sandeep Bagri; Subhash Chandra; S. Manickam; Satpal Singh; A. H. Prakash; Y. G. Prasad (Agricultural Research, 2025)

Evaluation of resistance in groundnut genotypes against leafhoppers - Burjikindi Madhuri; Rohini Sugandi; Subhash B. Kandakoor; B. S. Yenagi; Kolli Bharghavi (International Journal of Tropical Insect Science, 2025)

The SAP-1 payload: A technology demonstration for space-based microbiology experiments - A. Lokaveer; Vikram Khaire; Thomas Anjana; Maliyekkal Yasir; S. Yogahariharan; Akash Dewangan; Saurabh Kishor Mahajan; Sakshi Aravind Tembhurne; Gunja Subhash Gupta; Devashish Bhalla; Anantha Datta Dhruva; Aloke Kumar; et al. (Advances in Space Research, 2025)

Influence of coloured shade nets on shoot and root growth of dragon fruit stem cuttings - Ajaypartap Singh; Subhash Chander; J. S. Brar (Vegetos, 2025)

Effects of in vitro cytochalasin D and hypoxia on mitochondrial energetics and biogenesis, cell signal status and actin/tubulin/Hsp/MMP entity in air-breathing fish heart - S. Rekha; M.C. Subhash Peter (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Piriformospora indica and Arbuscular Mycorrhizal Fungus suppress fungal root rot and mosaic diseases of cassava - Akhila P. Subhash; S. S. Veena; T. Makeshkumar; K. N. Anith (Symbiosis, 2025)

Pink Bollworm, Pectinophora gossypiella (Saunders) Infestation Escalates from Incipient to Serious Proportions in North Cotton Zone of India - Rishi Kumar; Debashis Paul; S. K. Sain; Amarpreet Singh; Subhash Chandra; Satpal Singh; Rupinder Singh Cheema; Y. G. Prasad (Journal of Crop Health, 2025)

Presence of emerging organic contaminants and microbial indicators in surface water and groundwater in urban India - Bentje Brauns; Subhash Chandra; Wayne Civil; Dan J. Lapworth; Alan M. MacDonald; Andrew A. McKenzie; Daniel S. Read; Muddu Sekhar; Andrew C. Singer; Amritha Thankachan; Holly J. Tipper (Environmental Pollution, 2024)

Feeding potential and foraging behaviour of cheilomenes sexmaculata (F.) on cotton whitefly, Bemisia tabaci (Gennadius) - Rakesh Kumar; Sachin S. Suroshe; Y. Venkanna; M. C. Keerthi; Anoop Kumar; Subhash Chander (International Journal of Tropical Insect Science, 2024)

Identification of synthetic wheat lines with broadly effective stripe rust resistance - Karanjeet S. Sandhu; Davinder Singh; Fikrte Y. Belayineh; Tamrat Negash; Hanif Khan; Subhash C. Bhardwaj; Suraj Baidya; Dhruba B. Thapa; Muhammad Fayyaz; Shahzad Asad; Mandeep S. Randhawa; Robert F. Park (Australasian Plant Pathology, 2024)
Wheat stripe/yellow rust (WYR), caused by Puccinia striiformis f. sp. tritici ( Pst ), is a major constraint in global wheat production. A set of 766 hexaploid synthetic wheat lines, including primary crosses of Triticum turgidum x Aegilops tauschii and their derivatives, were screened in artificially rust inoculated field nurseries for three seasons. From this set, a core set of 94 non-lodging lines with unique pedigrees and resistance to Pst that was consistent across years was established. The core set was tested for adult plant field response under field conditions for three seasons in Australia and at least one crop season in Ethiopia, India, Kenya, Nepal and Pakistan. It was also challenged with an array of well-defined Pst pathotypes at seedling growth stages in the greenhouse, and genotyped with molecular markers linked to the adult plant resistance (APR) genes Yr18 , Yr36 and Yr46 . Combined analysis of field rust responses, multi-pathotype seedling phenotyping and marker genotyping resolved seven classes of Pst resistance: uncatalogued (new) APR (UAPR, 11%), uncatalogued seedling resistance (USR, 46%), known seedling resistance (KSR, 5%), KSR + USR (2%), Yr18 + UAPR (4%), Yr18 + USR (29%) and Yr18 + KSR (3%). A majority of the lines carrying UAPR and USR either singly or in combination showed high levels of field resistance across all field sites and years of testing, demonstrating that these lines represent a valuable resource for breeding wheat for resistance to Pst .

Wheat as a new host for potato aphid Macrosiphum euphorbiae Thomas (Hemiptera: Aphididae) and construction of its age-stage two-sex life tables - Y. N. Venkatesh; S. Rajna; Sachin S. Suroshe; Sunil Joshi; Subhash Chander (Cereal Research Communications, 2024)

The Luna structure, India: A probable impact crater formed by an iron bolide - K.S. Sajinkumar; S. James; G.K. Indu; Saranya R. Chandran; Devika Padmakumar; J. Aswathi; S. Keerthy; M.N. Praveen; N. Sorcar; J.K. Tomson; Anil Chavan; Subhash Bhandari; et al. (Planetary and Space Science, 2024)

Sustaining Rice-Wheat System Through Integrated Nutrient Management via FYM or Sesbania Aculeata in India on Long Term Basis - Subhash Chander; S C. Tripathi; Karnam Venkatesh; R. P. Meena; Neeraj Kumar; R. S. Chhokar; Nitesh Kumar; Shiv Ram Samota; Deepa Sharma; Gyanendra Singh (International Journal of Plant Production, 2023)

Leaf explant based direct and indirect regeneration and SCoT marker assisted genetic fidelity analysis of endemic taxon Corynandra chelidonii var. pallae - Subhash Sirangi; Dulam Sandhya; Gulab Khan Rohela; Mahipal S. Shekhawat; Ragan Ajmeera; Vatsavaya S. Raju (Vegetos, 2023)

Measurement of radon concentration in soil gas and radon exhalation rate from soil samples along and across the Main Central Thrust of Garhwal Himalaya, India - Krishna Pal Singh; Subhash Chandra; Pooja Panwar; Abhishek Joshi; Ganesh Prasad; G. S. Gusain; R. C. Ramola (Environmental Geochemistry and Health, 2023)

Spatial distribution and optimum sample size for monitoring of water lily aphid Rhopalosiphum nymphaeae (L.) in Makhana Euryale ferox Salisb - Vinod K. Padala; N Ramya; Manoj Kumar; S Rajna; Mandla Rajashekhar; YN Venkatesh; SM Raut; Subhash Chander; IS Singh; Mohd. Monobrullah (International Journal of Tropical Insect Science, 2023)

Design, Development, and Evaluation of SA-F127:TPGS Polymeric Mixed Micelles for Improved Delivery of Glipizide Drug: In-vitro, Ex-vivo, and In-vivo Investigations - Hemil S. Patel; Bhavin A. Vyas; Subhash Tripathi; Rakesh K. Sharma (AAPS PharmSciTech, 2023)

Micro perforation based smart label to guide freshness of pasteurized milk packet - Subhash V. Pawde; Sachin R. Chaudhari; Rajeshwar S. Matche (Food Control, 2023)

Energy and carbon budgeting in a soybean–wheat system in different tillage, irrigation and fertilizer management practices in South-Asian semi-arid agroecology - G.A. Rajanna; Anchal Dass; Vinod K. Singh; Anil.K. Choudhary; Venkatesh Paramesh; Subhash Babu; Pravin K. Upadhyay; Manjanagouda S. Sannagoudar; B.C. Ajay; K. Viswanatha Reddy (European Journal of Agronomy, 2023)

A compendium of the best-preserved terrestrial hypervelocity impact crater in a basaltic terrain: The Lonar, India - Saranya R. Chandran; S. James; J. Aswathi; Devika Padmakumar; T. Sadeeda Marjan; R.B. Binoj Kumar; Anil Chavan; Subhash Bhandari; K.S. Sajinkumar (Earth-Science Reviews, 2023)

Climate plays a dominant role over land management in governing soil carbon dynamics in North Western Himalayas - Owais Ali Wani; Vikas Sharma; Shamal S. Kumar; Subhash Babu; K.R. Sharma; Sanjay Singh Rathore; Sudeep Marwaha; Nazir A. Ganai; S.R. Dar; Md Yeasin; Raghavendra Singh; Jaibir Tomar (Journal of Environmental Management, 2023)

Sustainability Assessment of Rice-Wheat System Through Organic Fertilizers and Green Manuring in Sub-Tropical Humid Climate - Subhash Chander; S. C. Tripathi; Karnam Venkatesh; Neeraj Kumar; R. P. Meena; R. S. Chhokar; Nidhi Kamboj; Nitesh Kumar (International Journal of Plant Production, 2023)

In-Silico molecular screening of natural compounds as a potential therapeutic inhibitor for Methicillin-resistant Staphylococcus aureus inhibition - Palanichamy Nandhini; Prashant Kr Gupta; Arun Kumar Mahapatra; Agneesh Pratim Das; Subhash Mohan Agarwal; Suresh Mickymaray; Abdulaziz S. Alothaim; Mariappan Rajan (Chemico-Biological Interactions, 2023)

Bioengineered dual fluorescent carbon nano dots from Indian long pepper leaves for multifaceted environmental and health utilities - Debadatta Mohapatra; Ravi Pratap; Vivek Pandey; Singh Shreya; Gaurav Gopal Naik; Subhash C. Mandal; Sunday O. Otimenyin; Pawan K. Dubey; Avanish S. Parmar; Alakh N. Sahu (Environmental Science and Pollution Research, 2023)

Fatty acids analysis, antioxidant, antimicrobial and biological activity of essential oil of Skimmia laureola Leaves - V. K. Bisht; A. K. Bhandari; L. S. Kandari; T. Negi; Subhash Chandra; Sarla Saklani; Santwana Palai; Bruna Caroline Gonçalves Vasconcelo de Lacerda; Henrique D. M. Coutinho (Vegetos, 2023)

Assessment of genetic diversity in Tecomella undulata by using ISSR markers - Vijay Daneva; R. S. Beniwal; Subhash Kajla; Anil Kumar Poonia; Manish Kumar; Kajal (Vegetos, 2023)

Deciphering host plant resistance mechanisms of rice genotypes resistant against Brown Planthopper - Prabhulinga Tenguri; Subhash Chander; Ranjith K. Ellur; P. S. Arya; Yogesh Yele (Euphytica, 2023)

Outbreak and Management of Serpentine Leaf Miner, Liriomyza huidobrensis (Blanchard) (Diptera: Agromyzidae), on Potato (Solanum tuberosum L.) Crop in India - Priyank Hanuman Mhatre; Shivaji Hausrao Thube; Om Navik; E. P. Venkatasalam; Sanjeev Sharma; Jagadeesh Patil; S. Subhash; K. L. Divya; Santosh Watpade; Thava Prakash Pandian; M. Abas Shah; Manoj Kumar (Potato Research, 2022)

Lonar Impact Crater, India: the Best-Preserved Terrestrial Hypervelocity Impact Crater in a Basaltic Terrain as a Potential Global Geopark - Saranya R. Chandran; S. James; J. Aswathi; Devika Padmakumar; R. B. Binoj Kumar; Anil Chavan; Vivek Bhore; Krishna Kajale; Subhash Bhandari; K. S. Sajinkumar (Geoheritage, 2022)

Geoarchaeological Heritage of Kachchh Region, Gujarat, Western India: Geotourism Potentials - Adarsh Thakkar; Jaypalsinh M Jadeja; S. V. Rajesh; Anil Chavan; G. S. Abhayan; Subhash Bhandari; Gaurav Chauhan; M. G. Thakkar (Geoheritage, 2022)

Micropropagation of endemic Corynandra chelidonii var. pallae (Cleomaceae) through nodal explants and validation of their genetic integrity by ISSR markers - Subhash Sirangi; Phanikanth Jogam; Gulab Khan Rohela; Ajmeera Ragan; Vatsavaya S. Raju (Vegetos, 2022)

Persistence evaluation of fluopyram + tebuconazole residues on mango and pomegranate and their risk assessment - Vandana Tripathy; Krishan Kumar Sharma; Soudamini Mohapatra; Lekha Siddamallaiah; Nagapooja Yogendraiah Matadha; Chidanand Shiveshankar Patil; Yogesh Subhash Saindane; Bhaidas Deore; Cherukuri Sreenivasa Rao; Kaushik D. Parmar; Nitesh S. Litoriya; Paresh G. Shah; et al. (Environmental Science and Pollution Research, 2022)

Interactions of six spotted ladybird beetle, Cheilomenes sexmaculata (F.) with its host Phenacoccus solenopsis Tinsley and Intraguild members - Geethu S.; Sachin S. Suroshe; Subhash Chander; Venkanna Y. (International Journal of Tropical Insect Science, 2022)

Seed longevity studies in wild type, cultivated and inter-specific recombinant inbred lines (RILs) of soybean [Glycine max (L.) Merr.] - Subhash Chandra; Akshay Talukdar; Yashpal Taak; Raju R. Yadav; Manisha Saini; N. S. Sipani (Genetic Resources and Crop Evolution, 2022)

Ferrous Iron Overload Evokes Thyroidal and Interrenal Activation, Shifts Metabolite Pattern and Reverses Hepatic Ion Transporter Activities in Salinity-Acclimated Air-Breathing Fish (Anabas testudineus) Bloch - R. Gayathry; Valsa S. Peter; M. C. Subhash Peter (Proceedings of the Zoological Society, 2021)

Feeding potential and foraging behaviour of Cheilomenes sexmaculata (F.) on the cotton aphid, Aphis gossypii glover - Y. Venkanna; Sachin S. Suroshe; Subhash Chander; Sweetee Kumari (International Journal of Tropical Insect Science, 2021)

Conservational Tillage and Weed Management Practices Enhance Farmers Income and System Productivity of Rice–Wheat Cropping System in Central India - Dibakar Ghosh; C. R. Chethan; Subhash Chander; Bhumesh Kumar; R. P. Dubey; H. S. Bisen; S. K. Parey; P. K. Singh (Agricultural Research, 2021)

Novel role of photoinsensitive alleles in adaptation of soybean [Glycine max (L.) Merr.] to rainfed short growing seasons of lower latitudes - Rachana Tripathi; Nisha Agrawal; Giriraj Kumawat; Sanjay Gupta; Mrinal Kuchlan; Shivakumar Maranna; Vennampally Nataraj; Punam Kuchlan; Gyanesh K. Satpute; Milind B. Ratnaparkhe; Vangala Rajesh; Subhash Chandra; et al. (Genetic Resources and Crop Evolution, 2021)

Assessing the risk of mango quarantine pest Deanolis sublimbalis Snellen under different climate change scenarios - Gundappa Baradevanal; Subhash Chander; P. D. Kamala Jayanthi; H. S. Singh; D. Srinivasa Reddy (Journal of Plant Diseases and Protection, 2021)

Lr80: A new and widely effective source of leaf rust resistance of wheat for enhancing diversity of resistance among modern cultivars - Subodh Kumar; Subhash C. Bhardwaj; Om P. Gangwar; Akanksha Sharma; Naeela Qureshi; Vikas V. Kumaran; Hanif Khan; Pramod Prasad; Hanif Miah; Gyanendra P. Singh; Kiran Sharma; Hemlata Verma; et al. (Theoretical and Applied Genetics, 2021)

Identification of novel genetic sources for agronomic and quality traits in soybean using multi-trait allele specific genic marker assays - Giriraj Kumawat; Shivakumar Maranna; Sanjay Gupta; Rachana Tripathi; Nisha Agrawal; Vijayata Singh; Vangala Rajesh; Subhash Chandra; Viraj Kamble; Vennampally Nataraj; Abhishek Bharti; Mahaveer P. Sharma; et al. (Journal of Plant Biochemistry and Biotechnology, 2021)

Three Decades of Nationwide Forest Cover Mapping Using Indian Remote Sensing Satellite Data: A Success Story of Monitoring Forests for Conservation in India - Subhash Ashutosh; P. S. Roy (Journal of the Indian Society of Remote Sensing, 2021)

Genome-wide association studies revealed novel stripe rust resistance QTL in barley at seedling and adult-plant stages - Sanjaya Gyawali; Sujan Mamidi; Shiaoman Chao; Subhash C. Bhardwaj; Pradeep S. Shekhawat; Rajan Selvakumar; Om P. Gangwar; Ramesh Pal Singh Verma (Euphytica, 2021)

Application of in vitro protein solubility for selection of microalgae biomass as protein ingredient in animal and aquafeed - G. Venkata Subhash; Neera Chugh; Supriya Iyer; Ashish Waghmare; Amar S. Musale; Rajesh Nandru; Rakhi Bajpai Dixit; Mahadev S. Gaikwad; Deepthi Menon; Rakesh Thorat; G.Raja Krishna Kumar; Vinod Nagle; et al. (Journal of Applied Phycology, 2020)

Mechanical properties, spectral vibrational response, and flow-field analysis of the aragonite skeleton of the staghorn coral (Acropora cervicornis) - Alejandro Carrasco-Pena; Mahmoud Omer; Bridget Masa; Zachary Shepard; Tyler Scofield; Samik Bhattacharya; Nina Orlovskaya; Boyce E. Collins; Sergey N. Yarmolenko; Jagannathan Sankar; Ghatu Subhash; David S. Gilliam; et al. (Coral Reefs, 2020)

Microbes involved in arsenic mobilization and respiration: a review on isolation, identification, isolates and implications - Payal Mazumder; Subhash Kumar Sharma; Kaling Taki; Ajay S. Kalamdhad; Manish Kumar (Environmental Geochemistry and Health, 2020)

Attenuation of cocaine seeking in rats via enhancement of infralimbic cortical activity using stable step-function opsins - Victória A. Müller Ewald; Benjamin J. De Corte; Subhash C. Gupta; Katherine V. Lillis; Nandakumar S. Narayanan; John A. Wemmie; Ryan T. LaLumiere (Psychopharmacology, 2019)

Indigenous underutilized vegetables for food and nutritional security in an island ecosystem - Shrawan Singh; L. B. Singh; D. R. Singh; Subhash Chand; S. K. Zamir Ahmed; V. N. Singh; S. Dam Roy (Food Security, 2018)

Spatiotemporal dynamics and genome‐wide association analysis of desiccation tolerance in Drosophila melanogaster - Subhash Rajpurohit; Eran Gefen; Alan O. Bergland; Dmitri A. Petrov; Allen G. Gibbs; Paul S. Schmidt (Molecular Ecology, 2018)
Water availability is a major environmental challenge to a variety of terrestrial organisms. In insects, desiccation tolerance varies predictably over spatial and temporal scales and is an important physiological determinant of fitness in natural populations. Here, we examine the dynamics of desiccation tolerance in North American populations of Drosophila melanogaster using: (a) natural populations sampled across latitudes and seasons; (b) experimental evolution in field mesocosms over seasonal time; (c) genome‐wide associations to identify SNP s/genes associated with variation for desiccation tolerance; and (d) subsequent analysis of patterns of clinal/seasonal enrichment in existing pooled sequencing data of populations sampled in both North America and Australia. A cline in desiccation tolerance was observed, for which tolerance exhibited a positive association with latitude; tolerance also varied predictably with culture temperature, demonstrating a significant degree of thermal plasticity. Desiccation tolerance evolved rapidly in field mesocosms, although only males showed differences in desiccation tolerance between spring and autumn collections from natural populations. Water loss rates did not vary significantly among latitudinal or seasonal populations; however, changes in metabolic rates during prolonged exposure to dry conditions are consistent with increased tolerance in higher latitude populations. Genome‐wide associations in a panel of inbred lines identified twenty‐five SNP s in twenty‐one loci associated with sex‐averaged desiccation tolerance, but there is no robust signal of spatially varying selection on genes associated with desiccation tolerance. Together, our results suggest that desiccation tolerance is a complex and important fitness component that evolves rapidly and predictably in natural populations.

Perspectives on medicinal properties of natural phenolic monoterpenoids and their hybrids - Jamatsing D. Rajput; Suresh D. Bagul; Umesh D. Pete; Chetan M. Zade; Subhash B. Padhye; Ratnamala S. Bendre (Molecular Diversity, 2018)

Agronomic fortification of rice grains with secondary and micronutrients under differing crop management and soil moisture regimes in the north Indian Plains - Anchal Dass; Subhash Chandra; Norman Uphoff; Anil K. Choudhary; Ranjan Bhattacharyya; K. S. Rana (Paddy and Water Environment, 2017)

Complete genome sequence analysis of chicken astrovirus isolate from India - Amrutlal K. Patel; Ramesh J. Pandit; Jalpa R. Thakkar; Ankit T. Hinsu; Vinod C. Pandey; Joy K. Pal; Kantilal S. Prajapati; Subhash J. Jakhesara; Chaitanya G. Joshi (Veterinary Research Communications, 2017)

Mechanical Properties of High Entropy Alloy Al0.1CoCrFeNi for Peripheral Vascular Stent Application - Karthik Alagarsamy; Aleksandra Fortier; Mageshwari Komarasamy; Nilesh Kumar; Atif Mohammad; Subhash Banerjee; Hai-Chao Han; Rajiv S. Mishra (Cardiovascular Engineering and Technology, 2016)

Effect of Sowing Date and Cultivars on Aphid Infestation in Wheat with Climate Change Adaptation Perspective - Subhash Chander; Mazhar Husain; Vishwa Pal; Himanshu Pathak; S. D. Singh; Ramesh Harit; Vinod Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Human dipeptidyl peptidase III mRNA variant I and II are expressed concurrently in multiple tumor derived cell lines and translated at comparable efficiency in vitro - Subhash C. Prajapati; Shyam S. Chauhan (Molecular Biology Reports, 2016)

Effect of plant growth regulators on in vitro plant regeneration of sandalwood (Santalum album L.) via organogenesis - C. K. Singh; Sandeep R. Raj; P. S. Jaiswal; V. R. Patil; B. S. Punwar; J. C. Chavda; N. Subhash (Agroforestry Systems, 2016)

Influence of field re-ponding pattern and plant spacing on rice root–shoot characteristics, yield, and water productivity of two modern cultivars under SRI management in Indian Mollisols - Anchal Dass; Subhash Chandra; Anil K. Choudhary; Gurvinder Singh; S. Sudhishri (Paddy and Water Environment, 2016)

De novo design and in-silico studies of novel 1-phenyl-2,3,4,9-tetrahydro-1H-pyrido[3,4-b]indole-3-carboxylic acid derivatives as HIV-1 reverse transcriptase inhibitors - Ashok Penta; Subhash Chander; S. Ganguly; S. Murugesan (Medicinal Chemistry Research, 2014)

Interactions of bacteria with diatoms: influence on natural marine biofilms - Lidita Khandeparker; Priya M. D'Costa; Arga C. Anil; Subhash S. Sawant (Marine Ecology, 2014)
Interactions between microfouling components influence the biofilm community and the cascading events, thus playing an important role in the biofouling process. Bacteria and diatoms are among the dominant forms reported in biofilms. Experiments were carried out with natural marine biofilms from a tropical monsoon‐influenced environment to evaluate the interactions between bacteria and diatoms through application of antibiotics (streptomycin and chloramphenicol). Overall, chloramphenicol inhibited diatom communities, whereas streptomycin did not. These antibiotic‐mediated changes in the fouling diatom community were consistent across the seasons. However, the rates at which the fouling communities changed depended on the initial species composition. It was also observed that elevated nutrient concentrations overrode the inhibitory effect of chloramphenicol. Maximum V ibrio enhancement was observed in the enriched conditions during the pre‐monsoon and unenriched conditions during the monsoon (with naturally elevated background nutrient concentrations), highlighting the relevance of nutrient concentrations for V ibrio spp. This has interesting implications for antibiotic‐mediated interactions between fouling diatom and bacterial communities under differing nutrient regimes. Although this study indicates the relevance of ‘cross‐talk’ at the microfouling level, understanding the effects of additional microbial products ( e.g . bacteriocins and peptidoglycan) on these community‐level interactions will represent a step forward.

Synthesis and QSAR studies of some novel disubstituted 1,2,4-triazoles as antimicrobial agents - Siva S. Panda; Subhash C. Jain (Medicinal Chemistry Research, 2014)

Reversal of boswellic acid analog BA145 induced caspase dependent apoptosis by PI3K inhibitor LY294002 and MEK inhibitor PD98059 - Anup S. Pathania; Amit Joshi; Suresh Kumar; Santosh K. Guru; Shashi Bhushan; Parduman R. Sharma; Wajid W. Bhat; Ajit K. Saxena; Jaswant Singh; Bhahwal A. Shah; Samar S. Andotra; Subhash C. Taneja; et al. (Apoptosis, 2013)

Preparation and characterization of solid lipid nanoparticle-based nasal spray of budesonide - Sandip S. Chavan; Subhash G. Ingle; Pradeep R. Vavia (Drug Delivery and Translational Research, 2013)

A transcriptomic approach for exploring the molecular basis for dosha-balancing property-based classification of plants in Ayurveda - Ashutosh K. Shukla; Maneesha Mall; Santosh K. Rai; Shefali Singh; Priya Nair; Gaurav Parashar; Ajit K. Shasany; Subhash C. Singh; Vinod K. Joshi; Suman P. S. Khanuja (Molecular Biology Reports, 2013)

Plant regeneration from leaf explants of mature sandalwood (Santalum album L.) trees under in vitro conditions - C. K. Singh; Sandeep R. Raj; V. R. Patil; P. S. Jaiswal; N. Subhash (In Vitro Cellular & Developmental Biology - Plant, 2013)

A Simple and Efficient In Vitro Mass Multiplication Procedure for Stevia rebaudiana Bertoni and Analysis of Genetic Fidelity of In Vitro Raised Plants Through RAPD - Arpan R. Modi; Ghanshyam Patil; Nitish Kumar; Amritpal S. Singh; N. Subhash (Sugar Tech, 2012)

Evaluation of ameliorative effect of quercetin in experimental model of alcoholic neuropathy in rats - Kiran S. Raygude; Amit D. Kandhare; Pinaki Ghosh; Arvindkumar E. Ghule; Subhash L. Bodhankar (Inflammopharmacology, 2012)

Synthesis and antimicrobial activity of some new 4-triazolylmethoxy-2H-chromen-2-one derivatives - Siva S. Panda; Ritu Malik; Mahesh Chand; Subhash C. Jain (Medicinal Chemistry Research, 2012)

Phenyltins in Surface Sediments of the Visakhapatnam Harbour, India - Sangeeta S. Jadhav; Saroj N. Bhosle; Venkat Krishnamurthy; Subhash Sawant (Bulletin of Environmental Contamination and Toxicology, 2012)

Metagenomic analysis of Surti buffalo (Bubalus bubalis) rumen: a preliminary study - Krishna M. Singh; Viral B. Ahir; Ajai K. Tripathi; Umed V. Ramani; Manisha Sajnani; Prakash G. Koringa; Subhash Jakhesara; Paresh R. Pandya; Dharamsi N. Rank; Duggirala S. Murty; Ramesh K. Kothari; Chaitanya G. Joshi (Molecular Biology Reports, 2012)

Isoiridomyrmecin rich essential oil from Nepeta erecta Benth. and its antioxidant activity - Dinesh S. Bisht; Subhash C. Joshi; Rajendra C. Padalia; Chandra S. Mathela (Natural Product Research, 2012)

Genetic diversity assessment of Gymnema sylvestre (Retz.) R. Br. ex Sm. populations from Western Ghats of Maharashtra, India - Mohd. Shahnawaz; Rahul L. Zanan; Kantilal V. Wakte; Sarika V. Mathure; Trupti D. Kad; Subhash S. Deokule; Altafhusain B. Nadaf (Genetic Resources and Crop Evolution, 2012)

A new species of portunid crab of the genus Charybdis (De Haan, 1833) (Crustacea: Decapoda: Brachyura) from Goa, India - Vinay P. Padate; Chandrashekher U. Rivonker; A. Chandrashekar Anil; Subhash S. Sawant; Venkat Krishnamurthy (Marine Biology Research, 2010)

Structure-Activity Studies on Therapeutic Potential of Thymoquinone Analogs in Pancreatic Cancer - Sanjeev Banerjee; Asfar S. Azmi; Subhash Padhye; Marjit W. Singh; Jubaraj B. Baruah; Philip A. Philip; Fazlul H. Sarkar; Ramzi M. Mohammad (Pharmaceutical Research, 2010)

Assessment of genetic fidelity of micropropagated date palm (Phoenix dactylifera L.) plants by RAPD and ISSR markers assay - Nitish Kumar; Arpan R. Modi; Amritpal S. Singh; Bhavesh B. Gajera; Armi R. Patel; Mukesh P. Patel; Naraynan Subhash (Physiology and Molecular Biology of Plants, 2010)

Effect of Novel Amino Acids and Dipeptides Substituted 3-Morpholino Arecoline Derivatives as Muscarinic Receptor 1 Agonists in Alzheimer’s Dementia Models - S. R. Ranganatha; Manish Malviya; Y. C. Sunil Kumar; K. Vinaya; D. S. Prasanna; M. N. Subhash; K. S. Rangappa (International Journal of Peptide Research and Therapeutics, 2009)

Influence of Intermittent and Continuous Modes of Water Supply on Domestic Water Consumption - Subhash P. Andey; Prakash S. Kelkar (Water Resources Management, 2009)

Sex determination in 6 bovid species by duplex PCR - Prashant; Digpal S. Gour; Prem P. Dubey; Anubhav Jain; Subhash C. Gupta; Balwinder K. Joshi; Dinesh Kumar (Journal of Applied Genetics, 2008)

Oxygenated chalcones and bischalcones as a new class of inhibitors of DNA topoisomerase II of malarial parasites - Shalini Srivastava; Shweta Joshi; Alok R. Singh; Sarika Yadav; A. S. Saxena; V. J. Ram; Subhash Chandra; J. K. Saxena (Medicinal Chemistry Research, 2008)

Using molecular markers to identify two major loci controlling carotenoid contents in maize grain - Subhash Chander; Y. Q. Guo; X. H. Yang; J. Zhang; X. Q. Lu; J. B. Yan; T. M. Song; T. R. Rocheford; J. S. Li (Theoretical and Applied Genetics, 2008)

Residue Evaluation of Controlled-Release Formulations of Imidacloprid Against Rice Leaf Folder - B. Ram Prasad; Vidya S. Singh; Subhash Chander; Jitendra Kumar (Bulletin of Environmental Contamination and Toxicology, 2007)

Kuth (Saussurea lappa) cultivation in the cold desert environment of the Lahaul valley, northwestern Himalaya, India: arising threats and need to revive socio-economic values - Chandra P. Kuniyal; Yashwant S. Rawat; Santaram S. Oinam; Jagdish C. Kuniyal; Subhash C. R. Vishvakarma (Biodiversity and Conservation, 2005)

NMI-1182, a gastro-protective cyclo-oxygenase-inhibiting nitric oxide donor - James L. Ellis; Michael E. Augustyniak; Edward D. Cochran; Richard A. Earl; David S. Garvey; Laura J. Gordon; David R. Janero; Subhash P. Khanapure; L. Gordon Letts; Terry L. Melim; Madhavi G. Murty; David J. Schwalb; et al. (Inflammopharmacology, 2005)

Effect of antimalarials treatment on rat liver lysosomal function—Anin vivo study - Samir P. Patel; Subhash D. Katewa; Surendra S. Katyare (Indian Journal of Clinical Biochemistry, 2005)

Assessment and monitoring of estuarine mangrove forests of Goa using satellite remote sensing - I. J. Singh; S. K. Singh; S. P. S. Kushwaha; Subhash Ashutosh; R. K. Singh (Journal of the Indian Society of Remote Sensing, 2004)

Changing crop biodiversity and resource use efficiency of traditional versus introduced crops in the cold desert of the northwestern Indian Himalaya: a case of the Lahaul valley - Jagdish C. Kuniyal; Subhash C.R. Vishvakarma; Gopal S. Singh (Biodiversity and Conservation, 2004)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)